Educational and Sex Differentials in Life Expectancies and Disability-Free Life Expectancies in São Paulo, Brazil, and Urban Areas in Mexico - Beltrán-Sánchez, Hiram (2013)
OBJECTIVES: To estimate transition probabilities between disability states, total life expectancy, and the latter’s decomposition into years spent disabled and disability-free by age, sex and education among older adults in São Paulo, Brazil, and urban areas in Mexico. METHODS: Applied a micro-simulation method (Interpolative Markov Chains) using longitudinal data. RESULTS: We found large between-country educational differences in incidence of and recovery from disability with higher rates in Mexico than in São Paulo, but no differences in mortality. Older adults in Mexico spent longer time being disability-free than in São Paulo for both levels of education. Males and females in São Paulo spent a larger fraction of their remaining life disabled at every age than their counterparts in urban areas in Mexico. DISCUSSION: There were educational differences in the prevalence of disability in São Paulo and urban areas in Mexico, and significant educational differences in disability incidence and recovery across sites.